FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PADI DI KECAMATAN PARIAMAN SELATAN KOTA PARIAMAN - Yanti Murni; Vitri Deliana (Ensiklopedia Social Review, 2019)
Pariaman noted to have an area of 2.502 ha of wetland covering an area of 1.845 ha of which or 73,74% of the total rice area has been put on the irrigation system for irrigation, while the rest is still a non irrigated paddy (rainfed). With the vast rice fields,pariaman can produce as many as 31.047 tonnes of rice down than the previous year which amounted to 32.093 tonnes of production.thisdecrese is caused by reduction of rice area that has been put on irrigation system. From the multiple regression analysis, we can know that if the land area, selling price, production cost and production amount are zero or constant, the farmer's income will increase by 148.215. If there is an increase in land area of one unit, it will reduce farmer's income by 19.213.If there is an increase in Selling Price of one unit, it will increase farmer's income by 116.502. If there is an increase in Production Cost in one unit it will reduce farmer's income by 37.619. If there is an increase in Production of one unit, it will reeduce farmer's income by 76.305.